Peran Ayah dalam Menanamkan Sikap Self Acceptance dalam Rangka Mencegah Perilaku Homoseksual pada Anak - Isyatul Mardiyah (PSGA LP2M IAIN Pontianak, 2016)
The role of a father in a family is not only as a leader and living-earner. However, a father also has a rule to build children personality like self-acceptance so in the next days they could be great people. Moreover, there is an assumption that one of the reason the existence of LGBT people due to lack of father’s role at home. In addition, self-acceptance is one of significant factors in building one’s personality and behavior. Psychological issues such as hysteric feelings, sexual impotence, kleptomaniac, etc occurs because of lack of self-acceptance. Therefore, self-acceptance is also important for people who eager to recover from their illness since without the self-acceptance people would be in the pain, an introvert, hopeless, and isolated themselves from others.